Effectiveness of Inactivated SARS-CoV-2 Vaccines During a Delta Variant Outbreak in Hunan Province, China: A Retrospective Cohort Study - Xuemei Yan; Zhihui Dai; Qianhui Wu; Xiaolei Wang; Yan Wang; Ge Zeng; Yanpeng Wu; Shengbao Chen; Lan Yi; Hongjie Yu; Lidong Gao (Zoonoses, 2022)
This study was aimed at investigating the effectiveness of inactivated COVID-19 vaccines against the Delta variant. We performed a retrospective cohort study of close contacts of people with laboratory-confirmed SARS-CoV-2 infections in Hunan province, China, from July to August 2021. Mixed-effect logistic regression was used to estimate vaccine effectiveness (VE), and analyze the effects of the vaccination status of index cases and the exposure risk level on VE estimation. A total of 1,685 close contacts of 126 index cases were included; 835 (49.6%) had received two doses of inactivated vaccines, and the median interval between the 2nd dose and exposure was 48 days (IQR: 41 to 56 days). Full vaccination was defined as two doses at least 14 days before exposure. Adjusted VE estimates for full vaccination were 54.8% (95% CI: 7.7 to 77.9) and 68.4% (95% CI: 8.5 to 89.1) against symptomatic and moderate-to-severe COVID-19, respectively. VE for inactivated vaccines was difficult to observe if index cases had been fully vaccinated. The estimated VE with respect to infection protection was lower among household than non-household contacts. Complete primary immunization of two-dose inactivated COVID-19 vaccines protected against SARS-CoV-2 Delta variant infection. Infection risk was higher among vaccinated household contacts than vaccinated non-household contacts.